Composite solid electrolyte coated positive electrode material as well as preparation method and application thereof

By coating the positive electrode material with composite solid electrolyte, the problems of side reactions and structural degradation of high-nickel ternary positive electrode material during charging and discharging are solved, and the higher cycle life and safety of lithium-ion batteries are achieved.

CN119503908APending Publication Date: 2025-02-25LIONGO (CHANGZHOU) NEW ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411648243.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

High-nickel ternary cathode materials are prone to electrode-electrolyte surface side reactions during charging and discharging, resulting in interface cracking and structural degradation, affecting the circulation and safety performance of lithium-ion batteries.

Method used

The positive electrode material is coated with a composite solid electrolyte, and the silicification treatment, radio frequency glow discharge treatment and graft modification are used to form a multi-layer organic-inorganic membrane structure to inhibit side reactions and structural degradation.

Benefits of technology

Effectively isolate the direct contact between the electrode surface and the electrolyte, stabilize the interface of the positive electrode material, and improve the cycle life and safety of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140301540000261
    Figure BDA0005140301540000261
  • Figure HDA0005140301800000011
    Figure HDA0005140301800000011
Patent Text Reader

Abstract

The invention provides a preparation method of a composite solid electrolyte coated positive electrode material. According to the invention, the silicon coupling agent is coated on the solid electrolyte, and a reticular retaining layer containing organic silicon is formed on the surface of the solid electrolyte, so that the stability of a material interface is effectively stabilized, the electrolyte is prevented from corroding an electrode material, and the rate capability and the cycling stability of a lithium-rich material are greatly improved. Then a cationic polymer is selected as a base membrane to be assembled into two layers of hybrid membranes to coat the outermost layer of the solid electrolyte, and then the crown ether lithium salt complex is introduced into the surface of the phospholipid / cationic polymer hybrid membrane, so that the occurrence of side reactions on the surface of an electrode is effectively inhibited, the structure of an active material is stabilized, and meanwhile, the thermal stability of the membrane is improved; and finally, the surface of the positive electrode material is coated with the composite solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite solid electrolyte coated positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are the main choice for energy storage in new energy vehicles. The market's demand for long driving range for new energy vehicles has prompted lithium-ion batteries to develop in the direction of high energy density, high safety, long life and low cost. It has promoted the development and research of its key component materials - high-performance positive electrode materials. At present, commercial positive electrode materials mainly include lithium manganese oxide, lithium iron phosphate and ternary systems (NCA, NMC). From the perspective of the driving range of electric vehicles, lithium-ion batteries with high nickel and high voltage ternary materials as positive electrodes have higher energy density and are one of the main choices. However, as the Ni content requirements of the ternary layered positive electrode become higher and higher, or the charging cut-off voltage becomes higher and higher, higher requirements are placed on the stability of the material, especially the structural stability of the positive electrode material directly affects the cycle performance and safety performance of lithium-ion batteries.

[0003] However, as positive electrode materials, high nickel materials are facing serious electrode-electrolyte surface side reactions during early charge and discharge, which lead to cracking of the positive electrode-electrolyte interface (CEI), and the decrease in cycle / voltage stability with the increase of nickel content and voltage, which is prone to produce intergranular microcracks, which seriously restricts their further development. Therefore, the research can construct a multi-component composite solid electrolyte coating on high nickel ternary positive electrode materials. Through the synergistic effect of different materials, side reactions and structural degradation can be suppressed, thereby improving the performance and stability of lithium-ion batteries to meet the requirements of new energy vehicles for long driving range, high safety, etc., and achieve better comprehensive performance.

[0004] At present, various methods have been used to inhibit the side reactions and structural degradation of high-nickel materials during the charge and discharge process, including material modification, such as achieving a core-shell structure, the incorporation of functional dopants, and the application of inorganic or organic surface coatings, including metal oxides, metal fluorides, metal phosphates and polymers. The latter method is relatively simple, and the protective coating formed can physically prevent contact with the surrounding atmosphere, while also stabilizing the interface between the positive electrode material and the electrolyte. However, the use of inorganic coatings usually requires an additional calcination step at several hundred degrees Celsius, which will significantly increase costs and complicate recycling. In addition, lithium-free coatings (inorganic or organic) will hinder the transmission of lithium through the interface with the electrolyte, especially when it exceeds a certain thickness, which will negatively affect the performance of the battery at high current density. Therefore, a stable surface interface layer of the positive electrode material can effectively isolate the direct contact between the electrode surface and the electrolyte, inhibit the occurrence of surface side reactions, and is also the most direct way to improve the lithium concentration at the interface of the high-nickel ternary positive electrode.

[0005] Providing a positive electrode material that can effectively isolate the electrode surface from direct contact with the electrolyte and inhibit the occurrence of surface side reactions has become a problem that needs to be solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0006] Figure 1 This is a schematic diagram of the structure of the composite solid electrolyte provided by the present invention. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide a composite solid electrolyte coated positive electrode material and a preparation method and application thereof. The composite solid electrolyte coated positive electrode material provided by the present invention can effectively isolate the direct contact between the electrode surface and the electrolyte, thereby ensuring the stability of the positive electrode material, while ensuring the release of more active lithium and obtaining more reversible capacity, thereby improving the cycle life of the positive electrode material.

[0008] The present invention provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0009] A) using a coupling agent to silicify the solid electrolyte to obtain a silicified solid electrolyte;

[0010] B) subjecting the silicified solid electrolyte to radio frequency glow discharge treatment and then exposing the silicified solid electrolyte to air to obtain a silicified solid electrolyte having peroxide groups on the surface;

[0011] C) mixing the complex of lithium ions and crown ether with a solution of a hybrid membrane to react, thereby obtaining a solution of a hybrid membrane containing lithium ions; the hybrid membrane is a cationic polymer skeleton grafted with phospholipids;

[0012] D) Mixing a siliconized solid electrolyte having peroxide groups on the surface and a solution of a hybrid membrane containing lithium ions with riboflavin, and performing grafting modification under a protective atmosphere and ultraviolet conditions to obtain a composite solid electrolyte.

[0013] Preferably, the solid electrolyte is selected from NASICON type solid electrolyte Li 1+x Al x Ti 2-x (PO4)3, 0≤x<1, Garnet-type solid electrolyte Li 3x La 2 / 3-x TiO3, Li 7-x Ln3Z 2-x M x O 12 , M is one or more of Nb, Al or Ta, 0≤x<1.

[0014] Preferably, in step A), the silicification method comprises the following steps:

[0015] mixing the coupling agent with water for hydrolysis, and adding an alkaline aqueous solution to obtain a coupling agent solution;

[0016] The coupling agent solution is mixed with the solid electrolyte, subjected to siliconization treatment, and then washed and dried to obtain a siliconized solid electrolyte;

[0017] Preferably, the coupling agent is selected from one or more of KH-550, propyltrimethoxysilane MPS and 3-aminopropyltriethoxysilane APS, and the mass concentration of the coupling agent in the coupling agent solution is 1-4%;

[0018] Preferably, the siliconization treatment is carried out for 2 to 6 hours.

[0019] Preferably, in step B), the RF glow discharge treatment adopts argon plasma RF glow discharge treatment, the RF of the RF glow discharge treatment is in the range of 15 to 35 W, the treatment time is in the range of 10 to 30 s, and the pressure is in the range of 0.4 to 0.8 Torr;

[0020] The exposure time in the air is 5 to 20 minutes.

[0021] Preferably, in step C), the method for preparing the hybrid membrane comprises the following steps:

[0022] mixing the phospholipid, the cross-linking agent and the organic solvent to obtain a mixed solution;

[0023] After incubating the mixed solution at a suitable temperature, a cationic polymer and a basic compound are added to react to obtain a reactant;

[0024] drying the reactant to obtain a hybrid membrane;

[0025] Preferably, the cationic polymer is selected from polylysine (PLL), polyethyleneimine (PEI), polypropyleneimine (PPI), and has a molecular weight of 1 to 2 kDa;

[0026] The phospholipid is selected from one or more of the phospholipids dioleylphosphatidylethanolamine (DOPE), dipalmitoylphosphatidylethanolamine (DPPE), dimyristoylphosphatidylethanolamine (DMPE), and distearoylphosphatidylethanolamine (DLPE).

[0027] The mass ratio of the phospholipid to the solid electrolyte matrix is ​​in the range of 2:10 to 7:10, and can be 2:10, 3:10, 4:10, 5:10, 6:10, 7:10, or any value between 2:10 and 7:10.

[0028] The organic solvent is selected from chloroform or methanol, and the dosage ratio of the phospholipid to the organic solvent is preferably 5-8mmol:(200-500)mL, specifically 6.5mmol:300mL, 7mmol:500mL, 6mmol:200mL, 5.4mmol:500mL, 5mmol:400mL, or any value between 5-8mmol:(200-500)mL. The cross-linking agent is selected from N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDAC·HCl) or 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI), and the mass ratio of the cross-linking agent to the phospholipid is 1:1 to 1:10.

[0029] The basic compound is selected from one or more of trimethylamine, dimethylamine and triethylamine.

[0030] Preferably, in step C), the method for preparing the complex of lithium ion and crown ether comprises the following steps:

[0031] The aqueous solution of lithium salt is adjusted to pH, and then mixed with the organic solution of crown ether for reaction by stirring, and after removing the solvent, a complex of lithium ion and crown ether is obtained;

[0032] The crown ether is selected from one or more of 15-crown-5, benzo-15-crown-5, benzo-12-crown-4 and 12-crown-4;

[0033] The organic solvent for preparing the crown ether organic solution is selected from one or more of ethanol, benzene, chloroform, dichloromethane and ethyl acetate, and the concentration of the crown ether organic solution is 0.01-0.1 mol / L;

[0034] The lithium salt is selected from one or more of lithium fluoride, lithium chloride and lithium phosphate, the concentration of the lithium salt aqueous solution is 0.01-0.1 mol / L, and the pH value of the lithium salt solution is 6-9;

[0035] The stirring temperature is 40-70° C. and the stirring time is 1-4 hours.

[0036] Preferably, step C) comprises the following steps:

[0037] mixing the hybrid membrane with deionized water to obtain a hybrid membrane solution;

[0038] The lithium ion-crown ether complex and the hybrid membrane solution are subjected to high-speed shearing and mixing to obtain a hybrid membrane solution containing lithium ions;

[0039] Preferably, the concentration of the hybrid membrane solution is 5 to 20%;

[0040] The high-speed shearing time is 20 to 60 minutes.

[0041] Preferably, in step D), the protective atmosphere is argon;

[0042] The ultraviolet condition is ultraviolet light with a wavelength range of 350 to 380 nm;

[0043] The graft modification time is 20 to 36 hours.

[0044] The present invention also provides a composite solid electrolyte prepared by the above preparation method, comprising:

[0045] Solid electrolyte matrix;

[0046] A silicon layer composited on the surface of the solid electrolyte matrix;

[0047] A hybrid film composited on the surface of the silicon layer;

[0048] A crown ether complex layer is composited on the surface of the hybrid membrane.

[0049] The present invention also provides a positive electrode material coated with a composite solid electrolyte, comprising a positive electrode material matrix and the composite solid electrolyte coated on the surface of the positive electrode material matrix.

[0050] Preferably, the cathode material matrix is ​​selected from LiNi x Co y M 1-x-y O2, wherein 0.8≤x≤1, 0<y≤0.2, and M is at least one element selected from Al, Ba, Zr, Ti, Nb, and Ta.

[0051] The present invention also provides a method for preparing the composite solid electrolyte coated positive electrode material, which uses atomic layer deposition to form a composite solid electrolyte coating layer on the surface of the positive electrode material matrix powder.

[0052] Preferably, the preparation method comprises the following steps:

[0053] a) placing the cathode material matrix powder into a porous container, placing the porous container in a reaction chamber, evacuating the reaction chamber and replacing the nitrogen; dispersing the cathode material powder by fluidizing or rotating the porous container;

[0054] b) forming a composite solid electrolyte coating layer on the surface of the cathode material matrix powder by atomic layer deposition, including:

[0055] b01. Set the deposition process parameters: deposition temperature is 25-300°C, deposition pressure is 0.01-400 torr;

[0056] b02, introducing a composite solid electrolyte powder gas flow into the reaction chamber under nitrogen or argon gas, and maintaining the gas flow for 30 to 120 seconds;

[0057] b03. Purge the reaction chamber with nitrogen or argon;

[0058] b04. Repeat processes b01-b03 until the desired composite solid electrolyte coating thickness is deposited.

[0059] The present invention also provides a positive electrode plate, comprising the positive electrode material coated with the composite solid electrolyte.

[0060] Preferably, the positive electrode plate includes a current collector and a positive electrode material coating composited on the surface of the current collector, the positive electrode material coating includes a positive electrode material, and the positive electrode material includes the positive electrode material coated with the composite solid electrolyte according to claim 10 or 11.

[0061] Preferably, the positive electrode material coating further includes a conductive agent and a binder;

[0062] Preferably, the conductive agent is selected from any one or more of graphite, carbon black, and activated carbon;

[0063] The binder is selected from one or more of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and hydroxypropyl methylcellulose;

[0064] The mass ratio of the positive electrode material, the conductive agent and the binder is (80-95):(2-10):(2-10).

[0065] The present invention also provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.

[0066] Compared with the prior art, the present invention provides a preparation method of a composite solid electrolyte, comprising the following steps: A) using a coupling agent to perform silicification treatment on a solid electrolyte to obtain a silicified solid electrolyte; B) performing radio frequency glow discharge treatment on the silicified solid electrolyte and then exposing it in air to obtain a silicified solid electrolyte with a peroxide group on the surface; C) mixing a complex of lithium ions and crown ethers with a solution of a hybrid membrane to react, to obtain a solution of a hybrid membrane containing lithium ions; the hybrid membrane is a cationic polymer skeleton grafted with phospholipids; D) mixing a silicified solid electrolyte with a peroxide group on the surface and a solution of a hybrid membrane containing lithium ions with riboflavin, and performing grafting modification under a protective atmosphere and ultraviolet conditions to obtain a composite solid electrolyte. The present invention coats the solid electrolyte with a silicon coupling agent, and forms a mesh-like retaining layer containing organic silicon on its surface, which effectively stabilizes the stability of the material interface, prevents the electrolyte from corroding the electrode material, and greatly improves the rate performance and cycle stability of the lithium-rich material. Then, cationic polymers are selected as the base membrane to assemble into two layers of hybrid membranes to coat the outermost layer of the solid electrolyte. Finally, crown ether lithium salt complexes are introduced into the surface of the phospholipid / cationic polymer hybrid membrane, which effectively inhibits the occurrence of side reactions on the electrode surface, stabilizes the structure of the active material, and improves the thermal stability of the membrane and the interface ionic conductivity of the positive electrode material.

[0067] In addition, the composite solid electrolyte provided by the present invention forms a stable interface layer on the surface of the positive electrode material, which can effectively isolate the direct contact between the electrode surface and the electrolyte and inhibit the occurrence of surface side reactions. At the same time, the interaction between the organic / inorganic components in the composite solid electrolyte ensures the uniform distribution of different phases in the electrolyte, which helps the rapid migration of lithium ions around the interface. At the same time, it can also stabilize the interface between the positive electrode material and the electrolyte, reduce the activation energy of lithium ion migration in the electrolyte, and form a buffer layer on the surface of the positive electrode material, which can adapt to the volume expansion caused by the deintercalation of lithium ions in the positive electrode material, inhibit the generation of cracks in the positive electrode active material, and prevent the contact between the active material and the electrolyte, thereby ensuring the stability of the positive electrode material, while ensuring the removal of more active lithium, obtaining more reversible capacity, and thus improving the cycle life of the positive electrode material. DETAILED DESCRIPTION

[0068] The present invention provides a method for preparing a composite solid electrolyte, comprising the following steps:

[0069] A) using a coupling agent to perform silicification treatment on the solid electrolyte matrix to obtain a silicified solid electrolyte;

[0070] B) subjecting the silicified solid electrolyte to radio frequency glow discharge treatment and then exposing the silicified solid electrolyte to air to obtain a silicified solid electrolyte having peroxide groups on the surface;

[0071] C) mixing the complex of lithium ions and crown ether with a solution of a hybrid membrane to react, thereby obtaining a solution of a hybrid membrane containing lithium ions; the hybrid membrane is a cationic polymer skeleton grafted with phospholipids;

[0072] D) Mixing a siliconized solid electrolyte having peroxide groups on the surface and a solution of a hybrid membrane containing lithium ions with riboflavin, and performing grafting modification under a protective atmosphere and ultraviolet conditions to obtain a composite solid electrolyte.

[0073] In the present invention, the solid electrolyte matrix preferably adopts NASICON solid electrolyte Li 1+x Al x Ti 2-x (PO4)3, 0≤x<1, Garnet-type solid electrolyte Li 3x La 2 / 3-x TiO3, Li 7-x Ln3Z 2-x M x O 12 , M is one or more of Nb, Al or Ta, 0≤x<1.

[0074] The present invention first performs a silicification treatment on the solid electrolyte matrix. Specifically, the silicification treatment method includes the following steps:

[0075] The coupling agent is mixed with water for hydrolysis, and then a trace amount of alkaline aqueous solution is added to obtain a coupling agent solution; wherein the coupling agent is selected from one or more of KH-550, propyltrimethoxysilane (MPS) and 3-aminopropyltriethoxysilane (APS), and the hydrolysis time is 1 to 3 hours, which can be 1, 2, 3, or any value between 1 and 3 hours; the alkaline aqueous solution is preferably a 2M NaOH solution, and the mass concentration of the coupling agent in the coupling agent solution is 1 to 4%, which can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or any value between 1 and 4%.

[0076] Then, the coupling agent solution is mixed with the solid electrolyte for siliconization treatment, and then washed and dried to obtain a siliconized solid electrolyte; preferably, the siliconization treatment time is 2 to 6 hours, which can be 2, 3, 4, 5, 6, or any value between 2 and 6 hours; the present invention has no special restrictions on the washing method, and the washing method known to those skilled in the art can be used. Preferably, the siliconized product is repeatedly rinsed with ethanol and water, and then stirred in deionized water for 1 to 4 hours, which can be 1, 2, 3, 4, or any value between 1 to 4 hours, to remove the adsorbed organic coupling agent. The drying temperature is preferably 80 to 110°C, which can be 80, 90, 100, 110, or any value between 80 and 110°C, and the time is 1 to 3 hours, which can be 1, 2, 3, or any value between 1 to 3 hours.

[0077] The present invention coats the silicon coupling agent on the solid electrolyte by a simple method, and forms a mesh retaining layer containing organic silicon on the surface, which effectively stabilizes the material interface, avoids electrolyte corrosion of the electrode material, and greatly improves the rate performance and cycle stability of the lithium-rich material.

[0078] In some specific embodiments of the present invention, MPS is selected to coat the solid electrolyte, and the trimethoxysilane group in the MPS can combine with the hydroxide on the surface of the solid electrolyte particles to form water and silicon-oxygen bonds. The stable silicon-oxygen bonds can withstand the action of the electrolyte and the high oxidation potential, can improve the stability of the interfacial polymer, prevent the side reaction between the electrolyte and the positive electrode material, reduce the loss of active substances, and thus inhibit capacity decay.

[0079] Next, the present invention performs radio frequency glow discharge treatment on the silicified solid electrolyte and then exposes the silicified solid electrolyte to air to obtain a silicified solid electrolyte having peroxide groups on the surface;

[0080] Wherein, the RF glow discharge treatment adopts argon plasma RF glow discharge treatment, and the conditions are that the RF range is 15 to 35 W, which can be 15, 20, 25, 30, 35, or any value between 15 and 35 W, the treatment time range is 10 to 30 s, which can be 10, 15, 20, 25, 30, or any value between 10 and 30 s, and the pressure range is 0.4 to 0.8 Torr, which can be 0.4, 0.5, 0.6, 0.7, 0.8, or any value between 0.4 and 0.8 Torr.

[0081] The exposure time in the air is 5 to 20 minutes, and can be 5, 10, 15, 20, or any value between 5 and 20 minutes.

[0082] The invention mixes the complex of lithium ion and crown ether with the solution of hybrid membrane to react, so as to obtain the solution of hybrid membrane containing lithium ion; the hybrid membrane is a cationic polymer skeleton grafted with phospholipid.

[0083] Wherein, the preparation method of the hybrid membrane comprises the following steps:

[0084] mixing the phospholipid, the cross-linking agent and the organic solvent to obtain a mixed solution;

[0085] After incubating the mixed solution at a suitable temperature, a cationic polymer and a basic compound are added to react to obtain a reactant;

[0086] The reactant is dried to obtain a hybrid membrane.

[0087] In the present invention, a mixed solution is first prepared. The phospholipid is selected from one or more of the phospholipids dioleylphosphatidylethanolamine (DOPE), dipalmitoylphosphatidylethanolamine (DPPE), dimyristoylphosphatidylethanolamine (DMPE), and distearoylphosphatidylethanolamine (DLPE); the crosslinker is selected from N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDAC·HCl) or 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI); the mass ratio of the crosslinker to the phospholipid is 1:1 to 1:10, and can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, or any value between 1:1 and 1:10; the organic solvent is selected from chloroform or methanol. The usage ratio of the phospholipid to the organic solvent is preferably 5-8mmol:(200-500)mL, specifically 6.5mmol:300mL, 7mmol:500mL, 6mmol:200mL, 5.4mmol:500mL, 5mmol:400mL, or any value between 5-8mmol:(200-500)mL.

[0088] After the mixed solution is obtained, the mixed solution is incubated at an appropriate temperature, and then the cationic polymer and the alkaline compound are added to react to obtain a reactant.

[0089] The incubation temperature is 30°C to 38°C, and can be 30, 32, 35, 36, 38, or any value between 30°C and 38°C, and the incubation time is 14h to 36h, and can be 14, 15, 16, 28, 20, 24, 25, 28, 30, 32, 35, 36, or any value between 14h and 36h. The incubation time is based on ensuring that the activation reaction is complete.

[0090] Then, a cationic polymer is added to the incubated solution, and then a basic compound is added to promote the reaction.

[0091] The cationic polymer is selected from one or more of polylysine (PLL), polyethyleneimine (PEI), and polypropyleneimine (PPI), and has a molecular weight of 1 to 2 kDa; the mass ratio of the cationic polymer to the solid electrolyte matrix is ​​in the range of 3:10 to 6:10, and can be 3:10, 4:10, 5:10, 6:10, or any value between 3:10 and 6:10.

[0092] The alkaline compound is selected from one or more of trimethylamine, dimethylamine and triethylamine, and the added amount is 1 to 10 times the amount of phospholipids in the mixed solution, and can be 1, 2, 3, 4, 5, 6, 7, 8, 9, or any value between 1 and 10 times.

[0093] The reaction temperature is room temperature, and the reaction time is 24 hours. In the present invention, room temperature is defined as 25±5°C.

[0094] Finally, the reaction product is dried to obtain a hybrid membrane, wherein the drying temperature is 80-100°C, and can be 80, 85, 90, 95, 100, or any value between 80-100°C, and the drying time is 1-3 hours, and can be 1, 2, 3, or any value between 1-3 hours.

[0095] The present invention uses a cationic polymer as a substrate to form a phospholipid / cationic polymer complex. The phospholipid can remain stable over a relatively wide range of temperatures and acidity and alkalinity, and can be evenly distributed on the surface of the positive electrode material, thereby improving the stability of the positive electrode material and reducing its dissolution and decomposition in the electrolyte, thereby helping to form a more stable CEI membrane.

[0096] In the present invention, the preparation method of the complex of lithium ion and crown ether comprises the following steps:

[0097] The pH of the aqueous solution of lithium salt is adjusted, and then the solution is mixed with the organic solution of crown ether and stirred to react. After the solvent is removed, a complex of lithium ions and crown ether is obtained.

[0098] The present invention prepares an aqueous solution of a lithium salt, and then uses hydrochloric acid to adjust the pH to obtain a lithium salt solution. The lithium salt is selected from one or more of lithium fluoride, lithium chloride and lithium phosphate. The concentration of the lithium salt aqueous solution is 0.01-0.1 mol / L, which can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or any value between 0.01-0.1 mol / L. The pH value of the lithium salt solution is 6-9, which can be 6, 6.5, 7, 7.5, 8, 8.5, 9, or any value between 6-9.

[0099] The present invention configures an organic solution of crown ether, wherein the crown ether has high selectivity for lithium ions, and the crown ether of the present invention is preferably one or more of 15-crown-5, benzo-15-crown-5, benzo-12-crown-4 and 12-crown-4; the organic solvent for configuring the organic solution of the crown ether is selected from one or more of ethanol, benzene, chloroform, dichloromethane and ethyl acetate, and the concentration of the organic solution of the crown ether is 0.01-0.1 mol / L.

[0100] After obtaining the lithium salt solution and the crown ether organic solution, the two are mixed and stirred to coordinate the crown ether with the lithium ion to form a complex, wherein the stirring temperature is 40 to 70° C., which can be 40, 50, 60, 70, or any value between 40 and 70° C., and the time is 1 to 4 hours, which can be 1, 2, 3, 4, or any value between 1 to 4 hours.

[0101] Finally, the solvent is removed to obtain a complex of lithium ions and crown ethers. The present invention has no particular limitation on the method for removing the solvent, and any method known to those skilled in the art can be used. In the present invention, the solvent is preferably removed by reduced pressure distillation.

[0102] The crown ether complex selected in the present invention is a complex containing a lithium salt, and the lithium salt is uniformly dispersed inside the coating layer formed by the crown ether layer, effectively preventing the electrolyte from directly contacting the electrode active material, and inhibiting the dissolution of the transition metal of the cathode material and the degradation of the surface structure during the film formation process, protecting the morphology and lattice structure of the electrode material, thereby significantly improving the capacity and cycle stability of the lithium ion battery.

[0103] After preparing the complex of lithium ion and crown ether and the hybrid membrane, a solution of the hybrid membrane containing lithium ions is prepared. Specifically, the steps include:

[0104] mixing the hybrid membrane with deionized water to obtain a hybrid membrane solution;

[0105] The hybrid membrane solution and the complex of lithium ions and crown ether are sheared at high speed and mixed to obtain a hybrid membrane solution containing lithium ions;

[0106] Preferably, the mass concentration of the solution of the hybrid membrane is 5-20%, which can be 5%, 10%, 15%, 20%, or any value between 5% and 20%; the high-speed shear time is 20-60 minutes, which can be 20, 30, 40, 50, 60, or any value between 20 and 60 minutes.

[0107] The present invention introduces the crown ether complex into the surface of the phospholipid / cationic polymer complex hybrid membrane, and forms a complex through the lithium ions in the crown ether complex and the nitrogen elements in the cationic polymer. The crown ether cavity ring provides more Li2O2 nucleation sites. During the charging process, the crown ether promotes the decomposition of Li2O2 to form defective Li+ through its strong binding force with Li+. 2-x O2, thereby improving the OER reaction kinetics, and also increasing the contact interface between the positive electrode material and the electrolyte, accelerating the oxidation of Li2O2, thereby improving reversibility, reducing the charge overpotential, and extending the cycle life.

[0108] Finally, the silicified solid electrolyte material with peroxide groups on the surface and the solution of the hybrid membrane containing lithium ions are mixed with riboflavin, and grafted and modified under a protective atmosphere and ultraviolet conditions to obtain a composite solid electrolyte.

[0109] Specifically, the silicified solid electrolyte with peroxide groups on the surface is immersed in a solution containing a hybrid membrane of lithium ions and mixed evenly, and then riboflavin is added, and then argon gas is introduced for 1-4 minutes to eliminate oxygen in the environment. The amount of riboflavin added is 2-6 mg, which can be 2, 3, 4, 5, 6, or any value between 2-6 mg. Usually, the amount of 1-5 g of the silicified solid electrolyte with peroxide groups on the surface is used as the added mass.

[0110] Finally, the surface is grafted and modified under a high-intensity ultraviolet lamp, wherein the ultraviolet condition is ultraviolet light with a wavelength range of 350 to 380 nm, the intensity of the ultraviolet light can be 350, 360, 370, 380, or any value between 350 and 380 nm, and the time for the grafting modification is 20 to 36 hours, which can be 20, 24, 28, 30, 35, 36, or any value between 20 and 36 hours.

[0111] Under the action of ultraviolet light, riboflavin produces reactive oxygen species, mainly singlet oxygen, which can react with the hybrid membrane to induce chemical cross-linking reactions between the amino groups (groups) therein, thereby increasing the mechanical strength of the hybrid membrane and ultimately obtaining a solid electrolyte with a lithium-ion-rich biofilm-like structure.

[0112] The present invention uses ultraviolet irradiation to decompose the peroxide groups in the silicone in the solid electrolyte into free radicals, and the phospholipid / cationic polymer complex is grafted on the surface of the positive electrode to construct a stable interface layer, thereby solving the problems of uneven coating and density, and improving the ionic conductivity of the surface of the positive electrode material, helping to construct an effective lithium ion migration network structure connecting the active material of the electrode, the conductive agent, and the current collector; in addition, it can also effectively inhibit the side reaction between the electrode and the electrolyte, while preventing the dissolution of cations, and maintaining the structural stability of the positive electrode material.

[0113] The present invention also provides a composite solid electrolyte prepared by the above preparation method, comprising:

[0114] Solid electrolyte matrix;

[0115] The silicon layer compounded on the surface of the solid electrolyte matrix has a thickness of 10 to 100 nm, which can be 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, or any value between 10 and 100 nm;

[0116] The hybrid film composited on the surface of the silicon layer has a thickness of 50 to 500 nm, which can be 50, 100, 150, 200, 250, 300, 350, 400, 450, 500, or any value between 50 and 500 nm;

[0117] The crown ether complex layer composited on the surface of the hybrid membrane has a thickness of 5 to 100 nm, which can be 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, or any value between 5 and 100 nm.

[0118] See also Figure 1 , Figure 1 This is a schematic structural diagram of the composite solid electrolyte provided by the present invention.

[0119] The present invention also provides a positive electrode material coated with a composite solid electrolyte, comprising a positive electrode material matrix and the composite solid electrolyte coated on the surface of the positive electrode material matrix.

[0120] Wherein, the positive electrode material matrix is ​​selected from LiNi x Co y M 1-x-y O2, wherein 0.8≤x≤1, 0<y≤0.2, and M is at least one element selected from Al, Ba, Zr, Ti, Nb, and Ta.

[0121] In the present invention, the composite solid electrolyte is coated on the surface of the positive electrode material matrix to form a composite solid electrolyte layer, and the thickness of the composite solid electrolyte layer is 1 to 10 nm, preferably 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or any value between 1 and 10 nm.

[0122] The present invention also provides a method for preparing a composite solid electrolyte coated positive electrode material, that is, forming a composite solid electrolyte coating layer on the surface of a positive electrode material matrix powder by using an atomic layer deposition method.

[0123] Specifically, the preparation method comprises the following steps:

[0124] a) placing the cathode material matrix powder into a porous container, placing the porous container in a reaction chamber, evacuating the reaction chamber and replacing the nitrogen; dispersing the cathode material powder by fluidizing or rotating the porous container;

[0125] b) forming a composite solid electrolyte coating layer on the surface of the cathode material matrix powder by atomic layer deposition, including:

[0126] b01. Set deposition process parameters: deposition temperature is 25-300°C, which can be 25, 50, 100, 150, 200, 250, 300, or any value between 25 and 300°C; deposition pressure is 0.01-400 torr, which can be 0.01, 0.1, 1, 5, 10, 50, 100, 200, 300, 400, or any value between 0.01 and 400 torr;

[0127] b02, introducing a composite solid electrolyte powder gas flow into the reaction chamber under nitrogen or argon gas, and maintaining the gas flow for 30 to 120 seconds;

[0128] b03. Purge the reaction chamber with nitrogen or argon;

[0129] b04. Repeat processes b01-b03 until the desired composite solid electrolyte coating thickness is deposited.

[0130] The present invention also provides a positive electrode sheet, which includes a positive electrode collector and a positive electrode material coating composited on the surface of the current collector, wherein the positive electrode material coating includes a positive electrode material, and the positive electrode material is a positive electrode material coated with a composite solid electrolyte prepared by the above-mentioned preparation method.

[0131] In the present invention, the positive electrode material coating further includes a conductive agent and a binder;

[0132] Preferably, the conductive agent is selected from any one or more of graphite, carbon black, and activated carbon;

[0133] The binder is selected from one or more of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and hydroxypropyl methylcellulose;

[0134] The mass ratio of the positive electrode material, the conductive agent and the binder is (80-95):(2-10):(2-10).

[0135] The present invention has no special restrictions on the preparation method of the positive electrode sheet, and any preparation method known to those skilled in the art can be used. Preferably, the present invention prepares the positive electrode sheet according to the following method:

[0136] The positive electrode material, the conductive agent, the binder and the solvent are mixed to obtain a positive electrode slurry. The slurry is coated on the current collector by a coating machine and dried. Preferably, the solvent is NMP and water.

[0137] Then, the electrode sheet is rolled at a pressure of 15-150 tons to obtain a high-nickel ternary positive electrode sheet.

[0138] The present invention also provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.

[0139] The present invention has the following beneficial effects:

[0140] 1. The present invention provides a composite solid electrolyte coated positive electrode material, wherein the silicon coating of the positive electrode active material reduces the generation of microcracks in the positive electrode material, improves the lithium ion migration at the positive electrode-electrolyte interface of the coating layer, thereby improving the cycle life and safety of the battery, and at the same time can withstand the action of the electrolyte and high oxidation potential, and can improve the stability of the polymer in the bionic membrane.

[0141] 2. The present invention provides a composite solid electrolyte coated positive electrode material, wherein the two layers of hybrid film coating in the positive electrode active material have good flexibility and adaptability, and can better adapt to the surface morphology and structure of the high-nickel positive electrode material, thereby improving the cycle stability and capacity retention rate of the battery. It can also effectively inhibit the side reaction between the electrode and the electrolyte, while preventing the dissolution of cations and maintaining the structural stability of the positive electrode material.

[0142] 3. The present invention provides a composite solid electrolyte coated positive electrode material, wherein the crown ether lithium salt complex introduced on the surface of the positive electrode active material increases the contact interface between the positive electrode material and the electrolyte, accelerates the oxidation of Li2O2, thereby improving the reversibility, reducing the charging overpotential, and extending the cycle life. At the same time, it also effectively prevents the electrolyte from directly contacting the electrode active material, protects the morphology and lattice structure of the electrode material, thereby significantly improving the capacity and cycle stability of the lithium-ion battery.

[0143] 4. The present invention prepares a composite solid electrolyte coated positive electrode material, wherein a solid electrolyte is added to the positive electrode material to form a stable solid electrolyte interface layer on its surface, which reduces the dissolution of transition metal ions in the high energy density ternary positive electrode material in the electrolyte and enhances the safety of the battery; at the same time, it also alleviates the volume expansion and structural collapse of the high nickel ternary positive electrode material during the cycle, improving the Li + The transfer speed between the positive electrode and the electrolyte increases the capacity and cycle life of the battery.

[0144] In summary, the present invention provides a composite solid electrolyte coated positive electrode material, which has high ionic conductivity, certain flexibility, wettability and thermal stability. The positive electrode sheet prepared by the present invention can reduce the generation of microcracks in the positive electrode material in the application of lithium batteries, and at the same time can withstand the action of the electrolyte and high oxidation potential, so that the lithium battery has obvious stability. This feature is not available in other high-nickel positive electrode sheets. The difference from other high-nickel positive electrode sheets is that a multi-layer organic-inorganic membrane is established to wrap the high-nickel ternary material, and a network structure for lithium ion transportation connecting the active material of the electrode sheet, the conductive agent, and the current collector is constructed; in addition, the side reaction between the electrode sheet and the electrolyte can be effectively inhibited, while preventing the dissolution of cations, maintaining the structural stability of the positive electrode material, and the excellent flexibility of the multiple membranes helps to improve the effective interface contact with the negative electrode electrolyte, thereby constructing a uniform Li + Diffusion layer. This feature is rarely available in other coating methods, so the composite solid electrolyte coated positive electrode material prepared by the present invention can achieve multiple technical effects in lithium battery applications.

[0145] In order to further understand the present invention, the composite solid electrolyte coated positive electrode material provided by the present invention and its preparation method and application are described below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0146] Example 1

[0147] 1. Material preparation

[0148] 1. Prepare 200 ml of 1% KH-550 ethanol solution, add 100 ml of deionized water and stir for 1 hour to hydrolyze the KH-550 solution, then add 1.5 ml of alkaline aqueous solution (the alkaline aqueous solution is 2 mol / L NaOH aqueous solution), and then add Li 1.3 Al 0.3 Ti 1.7 (PO4)3 was immersed in the above KH-550 solution for 5 hours for siliconization. The siliconized sample was repeatedly rinsed with ethanol and water, stirred in deionized water for 1 hour to remove the adsorbed KH-550, and finally dried at 110°C for 1 hour. The obtained sample was called LATP-KH.

[0149] 2. The obtained LATP-KH sample was treated with argon plasma RFGD (25W, 20s, 0.6Torr) and then exposed to the atmosphere for 15min to form peroxide groups on its surface.

[0150] 3. Dissolve DPPE (6.75 mmol) in 300 ml chloroform, add 2 g EDC·HCl and stir evenly. Incubate the reaction mixture at 30°C for 15 h, then add 1.5 kDa (5.2 mmol) PLL. Add 1.99 g trimethylamine, stir at room temperature for 24 h, and finally dry at 100°C for 2 h to obtain a DPPE / PLL hybrid membrane.

[0151] 4. Dissolve lithium chloride and benzo-15-crown-5 in distilled water and ethanol respectively to prepare a lithium salt solution and an organic phase solution with a uniform concentration of 0.05 mol / L. Add 0.2M HCl hydrochloric acid to the lithium salt solution to prepare a lithium salt solution with a pH value of 6.5. Then add the prepared organic phase and mix at 50°C with stirring for 2 hours. Then remove the solvent by reduced pressure distillation to obtain a benzo-15-crown-5 complex.

[0152] 5. The DPPE / PLL hybrid membrane was mixed with deionized water to prepare an 8% DPPE / PLL solution, which was then mixed with the benzo-15-crown-5 complex using a high shear mixer for 40 minutes to obtain a Li-containing + DPPE / PLL solution.

[0153] 6. Li + The DPPE / PLL solution was placed in a transparent polystyrene round-bottom tube and the plasma-treated LATP-KH sample was immersed in a solution containing Li + The DPPE / PLL solution was mixed and placed in a transparent polystyrene round-bottom tube, 3 mg of riboflavin was added, and argon was introduced for 2 minutes to eliminate oxygen in the environment. Then, the surface was grafted under a high-intensity ultraviolet lamp (350 nm) for 20 hours.

[0154] 7. LiNi 0.8 Co 0.1 Al 0.1 O2 powder is placed in a porous container, and the porous container is placed in a reaction chamber. The reaction chamber is evacuated and replaced with nitrogen at least twice to remove oxygen and water between particles or in pores to avoid residual and gas reaction. The reaction chamber is heated to 150°C and the pressure in the reaction chamber is maintained at 100 torr. The porous container is rotated to fully disperse the positive electrode material. The composite solid electrolyte prepared for atomic layer deposition is then pulsed into the reaction chamber under the influence of N2 and adsorbed on the LiNi 0.8 Co 0.1 Al 0.1O2 powder, and maintained for 60 seconds, and then purged with N2 for 30 seconds; similarly, water was pulsed into the reaction chamber under the influence of 5N2 until the pressure reached 200torr and maintained for 60 seconds; then purged with N2 for 30 seconds, thus completing an ALD deposition cycle; repeat the above ALD deposition cycle 20 times, that is, on LiNi 0.8 Co 0.1 Al 0.1 A uniform composite solid electrolyte coating layer is formed on the surface of the O2 powder to obtain a well-coated positive electrode material.

[0155] 2. Positive electrode current collector coating

[0156] The coated positive electrode material, conductive agent graphite, binder PVDF and NMP are mixed to obtain positive electrode slurry, wherein the mass ratio of the coated positive electrode material, conductive agent graphite and binder PVDF is 95:3:2. The slurry is coated on the current collector by a coating machine and dried. Then, it is rolled at a pressure of 30 tons to obtain the high-nickel ternary positive electrode sheet.

[0157] Example 2

[0158] 1. Material preparation

[0159] 1. Prepare 200 ml of 2% MPS ethanol solution, add 100 ml of deionized water and stir for 1 hour to hydrolyze the MPS solution, then add 1.5 ml of alkaline aqueous solution, the alkaline aqueous solution is 2 mol / L NaOH aqueous solution, and then soak LLZO in the above KH-550 solution for 5 hours for siliconization. The siliconized sample is repeatedly rinsed with ethanol and water, stirred in deionized water for 1 hour to remove the adsorbed MPS, and finally dried at 110 ° C for 1 hour. The obtained sample is called LLZO-MPS.

[0160] 2. The obtained LLZO-MPS sample was treated with argon plasma RFGD (20W, 25s, 0.7Torr) and then exposed to the atmosphere for 10min to form peroxide groups on its surface.

[0161] 3. Dissolve DOPE (6.5 mmol) in 300 ml chloroform, add 1.7 g EDC·HCl, and stir evenly. Incubate the reaction mixture at 35°C for 20 h, then add 1.7 kDa (34.7 mmol) PEI. Add 0.84 g triethylamine, stir at room temperature for 24 h, and finally dry at 95°C for 3 hours to obtain a DOPE / PEI hybrid membrane.

[0162] 4. Dissolve lithium fluoride and 15-crown-5 in distilled water and ethanol respectively to prepare a lithium salt solution and an organic phase solution with a uniform concentration of 0.07 mol / L. Add 0.2M HCl hydrochloric acid to the lithium salt solution to prepare a lithium salt solution with a pH value of 6.86. Then add the prepared organic phase and mix at 40°C with stirring for 3 hours. Then remove the solvent by reduced pressure distillation to obtain a 15-crown-5 complex.

[0163] 5. The DOPE / PEI hybrid membrane was mixed with deionized water to prepare 10% DOPE / PEI, and then mixed with 15-crown-5 complex using a high shear mixer for 50 minutes to obtain a DOPE / PEI solution containing Li+.

[0164] 6. Li + The plasma-treated LLZO-MPS sample was immersed in the DOPE / PEI solution containing Li+, mixed and placed in a transparent polystyrene round-bottom tube, 3.5 mg of riboflavin was added, and argon was introduced for 2 minutes to eliminate oxygen in the environment. Then, the surface was grafted under high-intensity ultraviolet light (360 nm) for 24 hours.

[0165] 7. LiNi 0.8 Co 0.1 Al 0.1 O2 powder is placed in a porous container, and the porous container is placed in a reaction chamber. The reaction chamber is evacuated and replaced with nitrogen at least twice to remove oxygen and water between particles or in pores to avoid residual and gas reaction. The reaction chamber is heated to 200°C and the pressure in the reaction chamber is maintained at 30 torr. The porous container is rotated to fully disperse the positive electrode material. The composite solid electrolyte prepared for atomic layer deposition is then pulsed into the reaction chamber under the influence of N2 and adsorbed on the LiNi 0.8 Co 0.1 Ni 0.1 O2 powder, and maintained for 80 seconds, and then purged with N2 for 60 seconds; similarly, water was pulsed into the reaction chamber under the N2 until the gas pressure reached 30torr and maintained for 80 seconds; then purged with N2 for 60 seconds, thus completing an ALD deposition cycle; repeat the above ALD deposition cycle 30 times, that is, on LiNi 0.8 Co 0.1 Al 0.1 A uniform composite solid electrolyte coating layer is formed on the surface of the O2 powder.

[0166] 2. Positive electrode current collector coating

[0167] The coated positive electrode material, conductive agent carbon black, binder PAA and NMP are mixed to obtain positive electrode slurry, wherein the mass ratio of the coated positive electrode material, carbon black and PAA is 92:6:2. The slurry is coated on the current collector by a coating machine and dried. Then, it is rolled at a pressure of 50 tons to obtain the high-nickel ternary positive electrode sheet.

[0168] Example 3

[0169] 1. Material preparation

[0170] 1. Prepare 200 ml of 3% APS ethanol solution, add 100 ml of deionized water and stir for 1 hour to hydrolyze the APS solution, then add 1.5 ml of alkaline aqueous solution (2 mol / L NaOH aqueous solution), and then add Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 The siliconized samples were immersed in the above APS solution for 5 hours. The siliconized samples were repeatedly rinsed with ethanol and water, stirred in deionized water for 1 hour to remove the adsorbed APS, and finally dried at 110°C for 1 hour. The obtained samples were called Ta-LLZO-APS.

[0171] 2. The obtained Ta-LLZO-APS sample was treated with argon plasma RFGD (20W, 15s, 0.6Torr) and then exposed to the atmosphere for 15min to form peroxide groups on its surface.

[0172] 3. Dissolve DMPE (7 mmol) in 500 ml methanol, add 1.4 g EDCl and stir evenly. Incubate the reaction mixture at 38 °C for 30 h, then add 1.3 kDa (45.7 mmol) PPI. Add 2.04 g dimethylamine, stir at room temperature for 24 h, and finally dry at 90 °C for 2 hours to obtain a DMPE / PPI hybrid membrane.

[0173] 4. Dissolve lithium phosphate and benzo-12-crown-4 in distilled water and dichloromethane respectively to prepare a lithium salt solution and an organic phase solution with a uniform concentration of 0.08 mol / L. Add 0.2 M HCl hydrochloric acid to the lithium salt solution to prepare a lithium salt solution with a pH value of 6.86. Then add the prepared organic phase and mix at 50°C with stirring for 3 hours. Then remove the solvent by reduced pressure distillation to obtain a benzo-12-crown-4 complex.

[0174] 5. The DMPE / PPI hybrid membrane was mixed with deionized water to prepare 15% DMPE / PPI, and then mixed with benzo-12-crown-4 complex using a high shear mixer for 30 minutes to obtain a Li + DMPE / PPI solution.

[0175] 6. Li + The DMPE / PPI solution was placed in a transparent polystyrene round-bottom tube and the plasma-treated Ta-LLZO-APS sample was immersed in a solution containing Li + The DMPE / PPI solution was mixed and placed in a transparent polystyrene round-bottom tube, 4 mg of riboflavin was added, and argon was introduced for 3 minutes to eliminate oxygen in the environment. Then, the surface was grafted under a high-intensity ultraviolet lamp (370 nm) for 30 hours.

[0176] 7. LiNi 0.9 Co 0.1 O2 powder is placed in a porous container, and the porous container is placed in a reaction chamber. The reaction chamber is evacuated and replaced with nitrogen at least twice to remove oxygen and water between particles or in pores to avoid residual and gas reaction. The reaction chamber is heated to 250°C and the pressure in the reaction chamber is maintained at 200 torr. The porous container is rotated to fully disperse the positive electrode material. The composite solid electrolyte prepared for atomic layer deposition is then pulsed into the reaction chamber under the influence of N2 and adsorbed on the LiNi 0.9 Co 0.1 O2 powder, and maintained for 100 seconds, and then purged with N2 for 40 seconds; similarly, water was pulsed into the reaction chamber under the N2 until the gas pressure reached 30torr and maintained for 100 seconds; then purged with N2 for 40 seconds, thus completing an ALD deposition cycle; repeat the above ALD deposition cycle 35 times, that is, on LiNi 0.9 Co 0.1 A uniform composite solid electrolyte coating is formed on the surface of O2 powder

[0177] 8. The mass ratio of the prepared positive electrode material, activated carbon and SBR in the positive electrode slurry is 89:6:5.

[0178] 2. Positive electrode current collector coating

[0179] The coated positive electrode material, conductive agent activated carbon, binder SBR and NMP are mixed to obtain positive electrode slurry, wherein the mass ratio of the coated positive electrode material, activated carbon and SBR is 89:6:5. The slurry is coated on the current collector by a coating machine and dried. Then, it is rolled at a pressure of 55 tons to obtain the high-nickel ternary positive electrode sheet.

[0180] Example 4

[0181] 1. Material preparation

[0182] 1. Prepare 200 ml of 4% APS ethanol solution, add 100 ml of deionized water and stir for 1 hour to hydrolyze the APS solution, then add 1.5 ml of alkaline aqueous solution (2 mol / L NaOH aqueous solution), and then add Li 6.25 Al 0.25 La3Zr2O 12 The siliconized samples were immersed in the above APS solution for 5 hours. The siliconized samples were repeatedly rinsed with ethanol and water, stirred in deionized water for 1 hour to remove the adsorbed APS, and finally dried at 110°C for 1 hour. The obtained samples were called AL-LLZO-APS.

[0183] 2. The obtained AL-LLZO-APS sample was treated with argon plasma RFGD (25W, 20s, 0.6Torr) and then exposed to the atmosphere for 15min to form peroxide groups on its surface.

[0184] 3. Dissolve DLPE (6 mmol) in 250 ml methanol, add 0.8 g EDCl and stir evenly. Incubate the reaction mixture at 20 °C for 25 h, then add 1.5 kDa (5.57 mmol) PEI. Add 1.79 g triethylamine, stir at room temperature for 24 h, and finally dry at 100 °C for 2 hours to obtain DLPE / PEI hybrid membrane.

[0185] 4. Dissolve lithium fluoride and 12-crown-4 in distilled water and chloroform respectively to prepare a lithium salt solution and an organic phase solution with a uniform concentration of 0.09 mol / L. Add 0.2M HCl hydrochloric acid to the lithium salt solution to prepare a lithium salt solution with a pH of 7.4. Then add the prepared organic phase and mix at 60°C with stirring for 2 hours. Then remove the solvent by reduced pressure distillation to obtain a 12-crown-4 complex.

[0186] 5. The DLPE / PEI hybrid membrane was mixed with deionized water to prepare 18% DLPE / PEI, and then mixed with benzene 12-crown-4 complex using a high shear mixer for 60 minutes to obtain a Li + DLPE / PEI solution.

[0187] 6. Li + The DLPE / PEI solution was placed in a transparent polystyrene round-bottom tube and the plasma-treated AL-LLZO-APS sample was immersed in a solution containing Li + The DLPE / PEI solution was mixed and placed in a transparent polystyrene round-bottom tube, 5.2 mg of riboflavin was added, and argon was introduced for 3 minutes to eliminate oxygen in the environment. Then, the surface was grafted under a high-intensity ultraviolet lamp (375 nm) for 30 hours.

[0188] 7. LiNi 0.9 Co 0.1 O2 powder is placed in a porous container, and the porous container is placed in a reaction chamber. The reaction chamber is evacuated and nitrogen is replaced at least twice to remove oxygen and water between particles or in pores to avoid residual and gas reaction. The reaction chamber is heated to 180°C and the pressure in the reaction chamber is maintained at 45torr. The porous container is rotated to fully disperse the positive electrode material. The composite solid electrolyte prepared for atomic layer deposition is then pulsed into the reaction chamber under the influence of N2 and adsorbed on LiNi 0.9 Co 0.1 O2 powder, and maintained for 90 seconds, and then purged with N2 for 40 seconds; similarly, water was pulsed into the reaction chamber under the N2 until the pressure reached 100torr and maintained for 90 seconds; then purged with N2 for 40 seconds, thus completing an ALD deposition cycle; repeat the above ALD deposition cycle 25 times, that is, on LiNi 0.9 Co 0.1 A uniform composite solid electrolyte coating layer is formed on the surface of the O2 powder.

[0189] 2. Positive electrode current collector coating

[0190] The coated positive electrode material, conductive agent activated carbon, binder SBR and NMP are mixed to obtain positive electrode slurry, wherein the mass ratio of the prepared positive electrode material, activated carbon and SBR is 88:5:7. The slurry is coated on the current collector by a coating machine and dried. Then, it is rolled at a pressure of 80 tons to obtain the high-nickel ternary positive electrode sheet.

[0191] Example 5

[0192] 1. Material preparation

[0193] 1. Prepare 200 ml of 2% MPS ethanol solution, add 100 ml of deionized water and stir for 1 hour to hydrolyze the MPS solution, then add 1.5 ml of alkaline aqueous solution (2 mol / L NaOH aqueous solution), and then add Li 6.4 Al 0.2 La3Zr2O 12 The siliconized samples were soaked in the above MPS solution for 5 hours. The siliconized samples were repeatedly rinsed with ethanol and water, stirred in deionized water for 1 hour to remove the adsorbed MPS, and finally dried at 110°C for 1 hour. The obtained samples were called AL-LLZO-MPS.

[0194] 2. The obtained AL-LLZO-MPS sample was treated with argon plasma RFGD (25W, 20s, 0.6Torr) and then exposed to the atmosphere for 18min to form peroxide groups on its surface.

[0195] 3. Dissolve DOPE (5.4 mmol) in 500 ml methanol, add 2.4 g EDAC·HCl, and stir evenly. Incubate the reaction mixture at 38°C for 36 h, then add 1.4 kDa (7.45 mmol) PEI. Add 0.27 g triethylamine, stir at room temperature for 24 h, and finally dry at 80°C for 3 hours to obtain a DOPE / PEI hybrid membrane.

[0196] 4. Dissolve lithium chloride and benzo-15-crown-5 in distilled water and ethyl acetate respectively to prepare a lithium salt solution and an organic phase solution with a uniform concentration of 0.1 mol / L. Add 0.2 M HCl hydrochloric acid to the lithium salt solution to prepare a lithium salt solution with a pH of 7.8. Then add the prepared organic phase and mix at 65°C with stirring for 3 hours. Then remove the solvent by reduced pressure distillation to obtain a benzo-15-crown-5 complex.

[0197] 5. The DOPE / PEI hybrid membrane was mixed with deionized water to prepare 18% DOPE / PEI, and then mixed with benzo-15-crown-5 complex using a high shear mixer for 30 minutes to obtain a Li + of DOPE / PEI solution.

[0198] 6. Li + The DOPE / PEI solution was placed in a transparent polystyrene round-bottom tube and the plasma-treated AL-LLZO-MPS sample was immersed in a solution containing Li + The DOPE / PEI solution was mixed and placed in a transparent polystyrene round-bottom tube, 3.9 mg of riboflavin was added, and argon was introduced for 3 minutes to eliminate oxygen in the environment. Then, the surface was grafted under a high-intensity ultraviolet lamp (375 nm) for 30 hours.

[0199] 7. LiNi 0.8 Co 0.1 Ti 0.1 O2 powder is placed in a porous container, and the porous container is placed in a reaction chamber. The reaction chamber is evacuated and replaced with nitrogen at least twice to remove oxygen and water between particles or in pores to avoid residual and gas reaction. The reaction chamber is heated to 350°C and the pressure in the reaction chamber is maintained at 200 torr. The porous container is rotated to fully disperse the positive electrode material. The composite solid electrolyte prepared for atomic layer deposition is then pulsed into the reaction chamber under the influence of N2 and adsorbed on the LiNi 0.8 Co 0.1 Ti 0.1O2 powder, and maintained for 60 seconds, and then purged with N2 for 50 seconds; similarly, water was pulsed into the reaction chamber under the N2 until the pressure reached 50torr and maintained for 60 seconds; then purged with N2 for 50 seconds, thus completing an ALD deposition cycle; repeat the above ALD deposition cycle 50 times, that is, on LiNi 0.8 Co 0.1 Ti 0.1 A uniform composite solid electrolyte coating layer is formed on the surface of the O2 powder.

[0200] 2. Positive electrode current collector coating

[0201] The coated positive electrode material, conductive agent graphite, binder PVDF and NMP are mixed to obtain positive electrode slurry, wherein the mass ratio of the coated positive electrode material, graphite and PVDF is 80:10:10. The slurry is coated on the current collector by a coating machine and dried. Then, it is rolled at a pressure of 85 tons to obtain the high-nickel ternary positive electrode sheet.

[0202] Example 6

[0203] 1. Material preparation

[0204] 1. Prepare 200 ml of 1% KH550 ethanol solution, add 100 ml of deionized water and stir for 1 hour to hydrolyze the KH550 solution, then add 1.5 ml of alkaline aqueous solution, the alkaline aqueous solution is 2 mol / L NaOH aqueous solution, and then 0.34 La 0.51 TiO 2.94 The siliconized samples were immersed in the above KH550 solution for 6 hours. The siliconized samples were repeatedly rinsed with ethanol and water, stirred in deionized water for 1 hour to remove the adsorbed KH550, and finally dried at 110°C for 1 hour. The obtained samples were called LATP-KH550.

[0205] 2. The obtained LATP-KH550 sample was treated with argon plasma RFGD (15W, 30s, 0.4Torr) and then exposed to the atmosphere for 20min to form peroxide groups on its surface.

[0206] 3. Dissolve DOPE (5 mmol) in 400 ml chloroform, add 0.59 g EDCl, and stir evenly. Incubate the reaction mixture at 30 °C for 35 h, then add 1 kDa (4.5 mmol) PLL. Add 0.78 g trimethylamine, stir at room temperature for 24 h, and finally dry at 80 °C for 1 hour to obtain DOPE / PLL hybrid membrane.

[0207] 4. Dissolve lithium chloride and 15-crown-5 in distilled water and dichloromethane respectively to prepare a lithium salt solution and an organic phase solution with a uniform concentration of 0.01 mol / L. Add 0.2M HCl hydrochloric acid to the lithium salt solution to prepare a lithium salt solution with a pH of 6. Then add the prepared organic phase and stir the mixture at 40°C for 1 hour. Then remove the solvent by reduced pressure distillation to obtain a 15-crown-5 complex.

[0208] 5. The DOPE / PLL hybrid membrane was mixed with deionized water to prepare 5% DOPE / PLL, and then mixed with 15-crown-5 complex using a high shear mixer for 20 minutes to obtain a Li + DOPE / PLL solution.

[0209] 6. Li + The DOPE / PLL solution was placed in a transparent polystyrene round-bottom tube and the plasma-treated LATP-KH550 sample was immersed in a solution containing Li + The DOPE / PLL solution was mixed and placed in a transparent polystyrene round-bottom tube, 2 mg of riboflavin was added, and argon gas was introduced for 1 min to eliminate oxygen in the environment. Then, the surface was grafted under a high-intensity ultraviolet lamp (350 nm) for 20 h.

[0210] 7. LiNi 0.9 Co 0.1 O2 powder is placed in a porous container, and the porous container is placed in a reaction chamber. The reaction chamber is evacuated and nitrogen is replaced at least twice to remove oxygen and water between particles or in pores to avoid residual and gas reaction. The reaction chamber is heated to 25°C and the pressure in the reaction chamber is maintained at 0.01 torr. The porous container is rotated to fully disperse the positive electrode material. Then, the composite solid electrolyte prepared for atomic layer deposition is pulsed into the reaction chamber under the influence of N2 and adsorbed on LiNi 0.9 Co 0.1 O 22 Powder, and keep it for 30 seconds, then purge with N2 for 70 seconds; water is pulsed into the reaction chamber under the N2 until the pressure reaches 0.01torr and keep it for 30 seconds; then purge with N2 for 70 seconds, thus completing an ALD deposition cycle; repeat the above ALD deposition cycle 15 times, that is, on LiNi 0.9 Co 0.1 A uniform composite solid electrolyte coating layer is formed on the surface of the O2 powder.

[0211] 2. Positive electrode current collector coating

[0212] The coated positive electrode material, conductive agent carbon black, PVDF and NMP are mixed to obtain positive electrode slurry, wherein the mass ratio of the coated positive electrode material, carbon black and PVDF is 80:10:10. The slurry is coated on the current collector by a coating machine and dried. Then, it is rolled at a pressure of 15 tons to obtain the high-nickel ternary positive electrode sheet.

[0213] Example 7

[0214] 1. Material preparation

[0215] 1. Prepare 200 ml of 2% APS ethanol solution, add 100 ml of deionized water and stir for 1 hour to hydrolyze the APS solution, then add 1.5 ml of alkaline aqueous solution (2 mol / L NaOH aqueous solution), and then add Li 1.3 Al 0.3 Ti 1.7 (PO4)3 was immersed in the above APS solution for 5 hours for siliconization. The siliconized sample was repeatedly rinsed with ethanol and water, stirred in deionized water for 1 hour to remove the adsorbed APS, and finally dried at 110 ° C for 1 hour. The obtained sample was called LATP-APS.

[0216] 2. The obtained LATP-APS sample was treated with argon plasma RFGD (30W, 20s, 0.7Torr) and then exposed to the atmosphere for 20min to form peroxide groups on its surface.

[0217] 3. Dissolve DLPE (6.2 mmol) in 400 ml methanol, add 1.9 g EDAC·HCl and stir evenly. Incubate the reaction mixture at 30°C for 35 h, then add 1.5 kDa (2.5 mmol) PPI. Add 1.57 g trimethylamine, stir at room temperature for 24 h, and finally dry at 90°C for 1 hour to obtain a DLPE / PPI hybrid membrane.

[0218] 4. Dissolve lithium fluoride and 12-crown-4 in distilled water and benzene respectively to prepare a lithium salt solution and an organic phase solution with a uniform concentration of 0.06 mol / L. Add 0.2 M HCl hydrochloric acid to the lithium salt solution to prepare a lithium salt solution with a pH of 7.5. Then add the prepared organic phase and mix at 50°C with stirring for 4 hours. Then remove the solvent by reduced pressure distillation to obtain a 12-crown-4 complex.

[0219] 5. The DLPE / PPI hybrid membrane was mixed with deionized water to prepare 20% DLPE / PPI, and then mixed with 12-crown-4 complex using a high shear mixer for 50 minutes to obtain a Li + DLPE / PPI solution.

[0220] 6. Li+ The DMPE / PPI solution was placed in a transparent polystyrene round-bottom tube and the plasma-treated LATP-APS sample was immersed in a solution containing Li + The DLPE / PPI solution was mixed and placed in a transparent polystyrene round-bottom tube, 4.6 mg of riboflavin was added, and argon was introduced for 2 minutes to eliminate oxygen in the environment. Then, the surface was grafted under a high-intensity ultraviolet lamp (365 nm) for 24 hours.

[0221] 7. LiNi 0.9 Co 0.1 O2 powder is placed in a porous container, and the porous container is placed in a reaction chamber. The reaction chamber is evacuated and replaced with nitrogen at least twice to remove oxygen and water between particles or in pores to avoid residual and gas reaction. The reaction chamber is heated to 300°C and the pressure in the reaction chamber is maintained at 400 torr. The porous container is rotated to fully disperse the positive electrode material. The composite solid electrolyte prepared for atomic layer deposition is then pulsed into the reaction chamber under the influence of N2 and adsorbed on LiNi 0.9 Co 0.1 O2 powder, and maintained for 30 seconds, and then purged with N2 for 70 seconds; similarly, water was pulsed into the reaction chamber under the N2 until the pressure reached 60torr and maintained for 30 seconds; then purged with N2 for 70 seconds, thus completing an ALD deposition cycle; repeat the above ALD deposition cycle 18 times, that is, on LiNi 0.9 Co 0.1 A uniform composite solid electrolyte coating layer is formed on the surface of the O2 powder.

[0222] 2. Positive electrode current collector coating

[0223] The coated positive electrode material, the conductive agent carbon black, the binder SBR and NMP are mixed to obtain a positive electrode slurry, wherein the mass ratio of the coated positive electrode material, carbon black and SBR is 91:6:3. The slurry is coated on the current collector by a coating machine and dried. Then, it is rolled at a pressure of 70 tons to obtain the high-nickel ternary positive electrode sheet.

[0224] Example 8

[0225] 1. Material preparation

[0226] 1. Prepare 200 ml of 4% MPS ethanol solution, add 100 ml of deionized water and stir for 1 hour to hydrolyze the MPS solution, then add 1.5 ml of alkaline aqueous solution (2 mol / L NaOH aqueous solution), and then add Li 1.3 Al 0.3 Ti 1.7(PO4)3 was immersed in the above MPS solution for 2 hours for siliconization. The siliconized sample was repeatedly rinsed with ethanol and water, stirred in deionized water for 1 hour to remove the adsorbed MPS, and finally dried at 80 °C for 3 hours. The obtained sample was called LATP-MPS.

[0227] 2. The obtained LATP-MPS sample was treated with argon plasma RFGD (35W, 10s, 0.8Torr) and then exposed to the atmosphere for 5min to form peroxide groups on its surface.

[0228] 3. Dissolve DMPE (8 mmol) in 300 ml methanol, add 0.58 g EDAC·HCl, and stir evenly. Incubate the reaction mixture at 30°C for 35 h, then add 2 kDa (2.7 mmol) PPI. Add 2.4 g trimethylamine, stir at room temperature for 24 h, and finally dry at 90°C for 1 hour to obtain a DMPE / PPI hybrid membrane.

[0229] 4. Dissolve lithium chloride and benzo-12-crown-4 in distilled water and ethyl acetate respectively to prepare a lithium salt solution and an organic phase solution with a uniform concentration of 0.1 mol / L. Add 0.2 M HCl to the lithium salt solution to prepare a lithium salt solution with a pH of 9. Then add the prepared organic phase and mix at 70°C with stirring for 4 hours. Remove the solvent by reduced pressure distillation to obtain a benzo-12-crown-4 complex.

[0230] 5. The DMPE / PPI hybrid membrane was mixed with deionized water to prepare 20% DMPE / PPI, and then mixed with benzo-12-crown-4 complex using a high shear mixer for 60 minutes to obtain a Li + DMPE / PPI solution.

[0231] 6. Li + The DMPE / PPI solution was placed in a transparent polystyrene round-bottom tube and the plasma-treated LATP-MPS sample was immersed in a solution containing Li + The DMPE / PPI solution was mixed and placed in a transparent polystyrene round-bottom tube, 6 mg of riboflavin was added, and argon was introduced for 2 minutes to eliminate oxygen in the environment. Then, the surface was grafted under a high-intensity ultraviolet lamp (380 nm) for 36 hours.

[0232] 7. LiNi 0.8 Co 0.1 Al 0.1O2 powder is placed in a porous container, and the porous container is placed in a reaction chamber. The reaction chamber is evacuated and replaced with nitrogen at least twice to remove oxygen and water between particles or in pores to avoid residual and gas reaction. The reaction chamber is heated to 300°C and the pressure in the reaction chamber is maintained at 400 torr. The porous container is rotated to fully disperse the positive electrode material. The composite solid electrolyte prepared for atomic layer deposition is then pulsed into the reaction chamber under the influence of N2 and adsorbed on LiNi 0.8 Co 0.1 Al 0.1 O2 powder, and maintained for 120 seconds, and then purged with N2 for 70 seconds; similarly, water was pulsed into the reaction chamber under the N2 until the gas pressure reached 400torr and maintained for 120 seconds; then purged with N2 for 70 seconds, thus completing an ALD deposition cycle; repeat the above ALD deposition cycle 15 times, that is, on LiNi 0.8 Co 0.1 Al 0.1 A uniform composite solid electrolyte coating layer is formed on the surface of the O2 powder.

[0233] 2. Positive electrode current collector coating

[0234] The coated positive electrode material, the conductive agent carbon black, the binder polyacrylic acid and NMP are mixed to obtain a positive electrode slurry, wherein the mass ratio of the coated positive electrode material, carbon black and polyacrylic acid is 95:2:3. The slurry is coated on the current collector by a coating machine and dried. Then, it is rolled at a pressure of 150 tons to obtain the high-nickel ternary positive electrode sheet.

[0235] Comparative Example 1

[0236] The positive electrode material coating layer was prepared according to the method of Example 1, but the hybrid film was grafted and modified under a low-intensity ultraviolet lamp (260 nm), and then the LiNi 0.8 Co 0.1 Al 0.1 O2 is used for coating.

[0237] Comparative Example 2

[0238] The positive electrode material coating layer was prepared according to the method of Example 1, but the hybrid film was grafted and modified under a medium-intensity ultraviolet lamp (300 nm), and then the LiNi 0.8 Co 0.1 Al 0.1 O2 coating comparative example 3

[0239] The positive electrode material coating layer was prepared according to the method of Example 1, but the sample was not treated with argon plasma RFGD (25W, 20s, 0.6Torr) before the solid electrolyte coating. 0.8Co 0.1 Al 0.1 O2 is used for coating.

[0240] Comparative Example 4

[0241] The positive electrode coating layer was prepared according to the method of Example 4, but in step 6 of Example 4, riboflavin was not added, and then LiNi 0.9 Co 0.1 O2 is used for coating.

[0242] Comparative Example 5

[0243] The positive electrode coating layer was prepared according to the method of Example 4, but without the solid electrolyte, and then the LiNi 0.9 Co 0.1 O2 is used for coating.

[0244] Comparative Example 6

[0245] The same uncoated positive electrode material LiNi as in Example 4 was selected. 0.9 Co 0.1 O2 directly prepares button cells for testing according to the testing method of the present invention.

[0246] Comparative Example 7

[0247] The same solid electrolyte as in Example 5 was selected, and the silanization treatment in step 1 was omitted, and the other steps were the same as in Example 5. Finally, a button cell was directly prepared and tested according to the test method of the present invention.

[0248] Comparative Example 8

[0249] The same solid electrolyte as in Example 5 was selected and subjected to silanization treatment, but the DOPE / PEI composite membrane in step 3 was not prepared, and the other steps were the same as in Example 5. Finally, a button cell was directly prepared and tested according to the test method of the present invention.

[0250] Comparative Example 9

[0251] The same solid electrolyte as in Example 6 was selected, and the crown ether lithium salt complex of step 4 was not added, and the other steps were the same as in Example 6. Finally, a button cell was directly prepared and tested according to the test method of the present invention.

[0252] Comparative Example 10

[0253] The coated positive electrode material was prepared according to Example 6, without atomic deposition coating, and the mass ratio of the prepared positive electrode material, composite solid electrolyte, carbon black, and hydroxypropyl methylcellulose in the positive electrode slurry was 91:6:3. The other steps were the same as in Example 6. Finally, a button cell was directly prepared according to the test method of the present invention for testing.

[0254] The positive electrode sheet obtained by the preparation method of Examples 1-6 and Comparative Examples 1-10 was punched into a 12 mm electrode sheet. The electrode sheet was dried in a vacuum drying oven at 120° C. for 12 hours, and then assembled into a CR2032 button battery in an argon-protected glove box (O2<1ppm, H2O<1ppm) with a lithium sheet as the negative electrode, the separator was polypropylene (PP), and the electrolyte was a 1 mol / L (LiPF6) and ethylene carbonate (EC) / dimethyl carbonate (DMC) (the volume ratio of EC and DMC was 1:2) solution.

[0255] The 2032 button cell was subjected to an electrochemical performance test at 25°C, and discharged at a rate of 0.1C for the first coulombic efficiency and first discharge specific capacity test, with a voltage range of 0.005-1.5V.

[0256] The initial charge and discharge capacity and 100 cycle capacity retention rate tests were carried out at 1C rate.

[0257] At the same time, the first charge and discharge battery capacity test was performed at a charging voltage of 2.8V-4.2V (voltage range) and 5C charging.

[0258] Table 1 shows the electrochemical performance of the embodiments of the present invention and the comparative examples.

[0259] Due to the different coating methods such as process parameters, it can be seen from the comparative data of Examples 1-8 and Comparative Examples 1-10 that, through the comparison of electrochemical performance, it can be found that the coating of the positive electrode material with the biofilm-like solid electrolyte prepared by the present invention significantly improves the first charge and discharge capacity of the positive electrode of the embodiment, which is due to the contribution of the pre-lithiation biofilm-like solid electrolyte to the positive electrode material. In addition, according to the first charge and discharge coulomb efficiency, 100 cycle capacity retention rate and different rate performance of the comparative example and the embodiment, it can be obtained that the electrochemical performance of the positive electrode prepared by the present invention is significantly improved in the application of the positive electrode material, which is due to the composite solid electrolyte providing protection and modification for the positive electrode material, reducing the occurrence of side reactions, and also improving the interface performance between the positive electrode material and the electrolyte, promoting the transmission of lithium ions, and significantly improving the cycle stability and rate performance of the positive electrode material. At the same time, combined with the joint action of pre-lithiation, the amount of lithium ions embedded in the battery during the first charge is further reduced, and the capacity and cycle life of the battery are improved.

[0260] Table 1

[0261]

[0262] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite solid electrolyte, characterized in that: The following steps are involved: A) using a coupling agent to silicify the solid electrolyte to obtain a silicified solid electrolyte; B) subjecting the silicified solid electrolyte to radio frequency glow discharge treatment and then exposing the silicified solid electrolyte to air to obtain a silicified solid electrolyte having peroxide groups on the surface; C) mixing the complex of lithium ions and crown ether with a solution of a hybrid membrane to react, thereby obtaining a solution of a hybrid membrane containing lithium ions; the hybrid membrane is a cationic polymer skeleton grafted with phospholipids; D) Mixing a siliconized solid electrolyte having peroxide groups on the surface and a solution of a hybrid membrane containing lithium ions with riboflavin, and performing grafting modification under a protective atmosphere and ultraviolet conditions to obtain a composite solid electrolyte.

2. The preparation method according to claim 1, characterized in that: The solid electrolyte is selected from NASICON type solid electrolyte Li 1+x Al x Ti 2-x (PO4)3, 0≤x<1, Garnet-type solid electrolyte Li 3x La 2 / 3-x TiO3, Li 7-x Ln3Z 2- x M x O 12 , M is one or more of Nb, Al or Ta, 0≤x<1.

3. The preparation method according to claim 1, characterized in that: In step A), the method of siliconization comprises the following steps: mixing the coupling agent with water for hydrolysis, and adding an alkaline aqueous solution to obtain a coupling agent solution; The coupling agent solution is mixed with the solid electrolyte, subjected to siliconization treatment, and then washed and dried to obtain a siliconized solid electrolyte; Preferably, the coupling agent is selected from one or more of KH-550, propyltrimethoxysilane and 3-aminopropyltriethoxysilane, and the mass concentration of the coupling agent in the coupling agent solution is 1 to 4%; Preferably, the siliconization treatment is carried out for 2 to 6 hours.

4. The preparation method according to claim 1, characterized in that: In step B), the radio frequency glow discharge treatment adopts argon plasma radio frequency glow discharge treatment, the radio frequency of the radio frequency glow discharge treatment ranges from 15 to 35W, the treatment time ranges from 10 to 30 seconds, and the pressure ranges from 0.4 to 0.8 Torr; The exposure time in the air is 5 to 20 minutes.

5. The preparation method according to claim 1, characterized in that: In step C), the method for preparing the hybrid membrane comprises the following steps: mixing the phospholipid, the cross-linking agent and the organic solvent to obtain a mixed solution; After incubating the mixed solution at a suitable temperature, a cationic polymer and a basic compound are added to react to obtain a reactant; drying the reactant to obtain a hybrid membrane; Preferably, the cationic polymer is selected from polylysine, polyethyleneimine, polypropyleneimine, and has a molecular weight of 1 to 2 kDa; The phospholipid is selected from one or more of the phospholipids dioleylphosphatidylethanolamine, dipalmitoylphosphatidylethanolamine, dimyristoylphosphatidylethanolamine, and distearoylphosphatidylethanolamine; The organic solvent is selected from chloroform or methanol; The cross-linking agent is selected from N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride or 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and the mass ratio of the cross-linking agent to the phospholipid is 1:1 to 1:10; The basic compound is selected from one or more of trimethylamine, dimethylamine and triethylamine.

6. The preparation method according to claim 1, characterized in that: In step C), the preparation method of the complex of lithium ion and crown ether comprises the following steps: The aqueous solution of lithium salt is adjusted to pH, and then mixed with the organic solution of crown ether for reaction by stirring, and after removing the solvent, a complex of lithium ion and crown ether is obtained; The crown ether is selected from one or more of 15-crown-5, benzo-15-crown-5, benzo-12-crown-4 and 12-crown-4; The organic solvent for preparing the crown ether organic solution is selected from one or more of ethanol, benzene, chloroform, dichloromethane and ethyl acetate, and the concentration of the crown ether organic solution is 0.01-0.1 mol / L; The lithium salt is selected from one or more of lithium fluoride, lithium chloride and lithium phosphate, the concentration of the lithium salt aqueous solution is 0.01-0.1 mol / L, and the pH value of the lithium salt solution is 6-9; The stirring temperature is 40-70° C. and the stirring time is 1-4 hours.

7. The preparation method according to claim 1, characterized in that: Step C) comprises the following steps: mixing the hybrid membrane with deionized water to obtain a hybrid membrane solution; The lithium ion-crown ether complex and the hybrid membrane solution are subjected to high-speed shearing and mixing to obtain a hybrid membrane solution containing lithium ions; Preferably, the concentration of the hybrid membrane solution is 5 to 20%; The high-speed shearing time is 20 to 60 minutes.

8. The preparation method according to claim 1, characterized in that: In step D), the protective atmosphere is argon; The ultraviolet condition is ultraviolet light with a wavelength range of 350 to 380 nm; The graft modification time is 20 to 36 hours.

9. A composite solid electrolyte prepared by the preparation method according to any one of claims 1 to 8, characterized in that: include: Solid electrolyte matrix; A silicon layer composited on the surface of the solid electrolyte matrix; A hybrid film composited on the surface of the silicon layer; A crown ether complex layer is composited on the surface of the hybrid membrane.

10. A positive electrode material coated with a composite solid electrolyte, characterized in that: The invention comprises a positive electrode material matrix and a composite solid electrolyte according to any one of claims 1 to 9 coated on the surface of the positive electrode material matrix.

11. The positive electrode material coated with a composite solid electrolyte according to claim 10, characterized in that: The positive electrode material matrix is ​​selected from LiNi x Co y M 1-x-y O2, wherein 0.8≤x≤1, 0<y≤0.2, and M is at least one element selected from Al, Ba, Zr, Ti, Nb, and Ta.

12. A method for preparing a positive electrode material coated with a composite solid electrolyte as claimed in claim 10 or 11, characterized in that: A composite solid electrolyte coating layer is formed on the surface of the cathode material matrix powder by atomic layer deposition.

13. The preparation method according to claim 12, characterized in that: The following steps are involved: a) placing the cathode material matrix powder into a porous container, placing the porous container in a reaction chamber, evacuating the reaction chamber and replacing the nitrogen; Dispersing the cathode material powder by fluidizing or rotating the porous container; b) forming a composite solid electrolyte coating layer on the surface of the cathode material matrix powder by atomic layer deposition, including: b01. Set deposition process parameters: deposition temperature is 25-300°C, deposition pressure is 0.01-400 torr; b02, introducing a composite solid electrolyte powder gas flow into the reaction chamber under nitrogen or argon gas, and maintaining the gas flow for 30 to 120 seconds; b03. Purge the reaction chamber with nitrogen or argon; b04. Repeat processes b01-b03 until the desired composite solid electrolyte coating thickness is deposited.

14. A positive electrode sheet, characterized in that: A positive electrode material coated with a composite solid electrolyte according to claim 10 or 11.

15. The positive electrode sheet according to claim 14, characterized in that: The positive electrode plate includes a current collector and a positive electrode material coating composited on the surface of the current collector, the positive electrode material coating includes a positive electrode material, and the positive electrode material includes the positive electrode material coated with the composite solid electrolyte according to claim 10 or 11.

16. The positive electrode sheet according to claim 14, characterized in that: The positive electrode material coating also includes a conductive agent and a binder; Preferably, the conductive agent is selected from any one or more of graphite, carbon black, and activated carbon; The binder is selected from one or more of polyvinylidene fluoride, polyacrylic acid, styrene-butadiene rubber, and hydroxypropyl methylcellulose; The mass ratio of the positive electrode material, the conductive agent and the binder is (80-95):(2-10):(2-10).

17. A lithium ion battery, characterized in that: A positive electrode sheet comprising any one of claims 14 to 16.

Citation Information

Cited By

  • Coated modified high-nickel ternary positive electrode material, preparation method and lithium ion battery

    CN120453330A